Heterozygosity in NPC may be associated with neurologic and systemic phenotypes - Tatiana Brémovà-Ertl; Sabina Tahirovic; Silva Katušić Hećimović; Kyriakos Martakis; Kyriakos Martakis; Marianne Rohrbach; Matthias Gautschi; Radhika Dhamija; Jaya Ganesh; Melinda Peters; Mark Walterfang; Susanne A. Schneider (Frontiers in Neurology)
BackgroundNiemann-Pick disease type C (NPC) is a pan-ethnic, progressive, recessively inherited lysosomal disorder that affects 1:100,000 live births. Emerging biochemical, genetic, and clinical evidence challenges the traditional view that disease-associated variants in the genes associated with the typical phenotype NPC manifest as an exclusively autosomal recessive disorder. While biallelic pathogenic variants cause the NPC disease phenotype, heterozygous carriers may exhibit phenotypic traits attributable to a partial loss of NPC1 or NPC2 function.MethodsWe conducted a literature search of articles relevant to heterozygosity in NPC genes and genes associated with other lysosomal diseases. A narrative mini-review format was employed with the intention of providing a brief overview of the frequency of NPC carriers, as well as the biochemical, genetic, non-clinical, and clinical evidence available for readers seeking to understand the scientific basis for why NPC heterozygosity should be discussed and considered as a potential risk factor for the development of neurological phenotype or neurodegenerative diseases.ConclusionHeterozygosity for many genes, including NPC1 variants, (“carriers” of a single variant in an NPC gene) can be clinically consequential. Recognizing the effects of NPC1 heterozygosity has profound implications for diagnosis, clinical monitoring, and potential early intervention. By broadening our understanding of the genetic and phenotypic spectrum of NPC, we can improve detection (which is straightforward in obligate heterozygotes, i.e., parents of NPC patients), reduce long-term health risks, and utilize targeted treatments that address the needs of carriers as well as affected individuals.